ANALISIS PENGGUNAAN DANA PROGRAM DESA MAJU INHIL JAYA (DMIJ) DENGAN METODE ANALYTICAL HIERARCHY PROCESS - Muh. Rasyid Ridha (Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir Riau, 2019)
The ability to make fast and careful decisions will be the key to success in global competition and to make a decision certainly requires a careful analysis and calculation, depending on the many criteria that affect the problems that require a decision. Taking a decision with many criteria requires a special way of handling. For this reason, a model is needed before a decision is made. The DMIJ Systematics Program is a District Government Program through the Empowerment approach by streamlining the functions of the Village Government, Village Institutions and Village Communities to plan, implement, preserve and supervise development in a participatory manner. To help in solving these problems there needs to be a decision support system. Decision support system is an interactive system that supports decisions in the decision making process through alternatives obtained from the results of data processing, information and model design. AHP is a decision support tool that can be used to solve complex decisions. The application of the AHP method in the development of decision support systems for the use of DMIJ regional government program funds is determined by 4 criteria: infrastructure, welfare, health, and education. The final result of this research is the type of activity that becomes the main priority to be used as a priority for the use of the budget in the DMIJ regional government program is the Supporting Road. Priorities obtained by the Supporting Road (JPN) with a total value of 0.404 or 40.4%. The most influential indicators were Infrastructure at 56.3%, then Kesra at 25.1%, Health 6.1% and, Education at 12.5%. Keywords : Use of Funds, DMIJ, SPK, AHP